Tinjauan Sejarah atas Peran Organisasi Kemasyarakatan Islam pada Pembangunan Indonesia - Dyah Rahmi Astuti; Muhammad Yusuf Wibisono (Jurnal Iman dan Spiritualitas, 2022)
This article aims to describe the role of Islamic community organizations in Indonesia's development. The method used in this paper is descriptive analysis. The discussion results show that Islamic organizations played a role in the struggle for independence in the cases of the Nahdlatul Ulama Jihad Resolution and the Muhammadiyah Jihad Mandate. The role of post-independence until now has been Nahdlatul Ulama Islamic Boarding School Education and Muhammadiyah Formal Education. Islamic organizations need to play an active role in Indonesia's development in terms of its role as a liaison between people's aspirations and the government. Also that Islamic organizations must increase their role in deradicalization programs to prevent terrorist acts and radicalism.